The antecedent factors of organizational performance - Afriany, Arista Natia (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2020)
Companies need human resources because with excelent human resources, corporate management will run well. This study objective is to examine the effect of work motivation, work discipline, work environment on job satisfaction and employee performance. The study was conducted at PT XXX with a total of 58 employees. This study uses structural analysis with smart PLS. The results showed that work motivation has an effect on job satisfaction and job satisfaction has an effect on employee performance. But work discipline and work environment do not affect job satisfaction. The results of this study have implications for companies to increase motivation and job satisfaction so that employee performance can be improved.